Direct Evidence of Magnetic Reconnection Onset via the Tearing Instability - Bakrania, Mayur R.; Rae, I. Jonathan; Walsh, Andrew P.; Verscharen, Daniel; Smith, Andy W.; Forsyth, Colin; Tenerani, Anna (Frontiers in Astronomy and Space Sciences, 2022)
Magnetic reconnection is a sporadic process responsible for energy release in space and laboratory plasmas. It is believed that the tearing mode instability may be responsible for the onset of reconnection in the magnetotail. However, due to its elusive nature, there is an absence of in-situ observations of the tearing instability prior to magnetic reconnection in our nearest natural plasma laboratory. Using neural network outlier detection methods in conjunction with Cluster spacecraft data, we find unique electron pitch angle distributions that are consistent with simulation predictions of the tearing instability and the subsequent evolution of plasma electrons and reconnection. We confirm that the events identified via our neural network outlier method are well above the tearing stability threshold based on the criterion detailed in this paper. We find signatures of magnetic reconnection minutes after the majority of tearing observations. Our analysis of the tearing instability provides new insights into the fundamental understanding of the mechanism responsible for reconnection, a process that is ubiquitous in different astrophysical plasma regimes across the universe and in laboratory experiments on Earth.